2007
DOI: 10.1007/s12012-007-9007-6
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between the Aryl Hydrocarbon Receptor and Hypoxia on the Constitutive Expression of Cytochrome P4501A1 mRNA

Abstract: Endothelial cells are a target of halogenated aromatic hydrocarbon toxicity following aryl hydrocarbon receptor (AHR) activation. Further, evidence suggests that AHR has a physiological function in endothelial cells in the absence of exogenous ligands. Understanding these "normal" functions of AHR may help to reveal the mechanisms that contribute to the toxicity of xenobiotic ligands. Thus, this study focused on the crosstalk between hypoxia and AHR in the absence of exogenous ligands. Constitutive CYP1A1 mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…Successful AHR inactivation was confirmed using methods reported elsewhere. 12 Inactivation of AHR in human microvascular endothelial cells isolated from lung significantly reduced prepro-ET-1 mRNA expression under normoxic conditions ( Figure 5A) but failed to alter hypoxia-induced expression ( Figure 5B) and had no effect on hypoxia-induced ET-1 secretion (data not shown). Similar results were obtained in studies conducted with human umbilical vein endothelial cells (data not shown).…”
Section: Lund Et Almentioning
confidence: 88%
“…Successful AHR inactivation was confirmed using methods reported elsewhere. 12 Inactivation of AHR in human microvascular endothelial cells isolated from lung significantly reduced prepro-ET-1 mRNA expression under normoxic conditions ( Figure 5A) but failed to alter hypoxia-induced expression ( Figure 5B) and had no effect on hypoxia-induced ET-1 secretion (data not shown). Similar results were obtained in studies conducted with human umbilical vein endothelial cells (data not shown).…”
Section: Lund Et Almentioning
confidence: 88%
“…Because AhR is reported to be involved in the constitutive expression of CYP1A1 (Zhang and Walker, 2007), the effect of SWCNTs on expression of AhR mRNA was investigated. However, the effect of SWCNTs on basal AhR expression was negligible in NHBE and A549 cells, indicating that the down-regulatory effect of SWCNTs on CYP1A1 mRNA was not due to the suppression of AhR expression.…”
Section: Discussionmentioning
confidence: 99%
“…29) Our results indicate that the downregulatory effect of SWCNTs on CYP1A1 mRNA was not due to the suppression of AHR expression. Resveratrol, a phenolic phytoalexin, downregulates both constitutive and polycyclic aromatic hydrocarbon-induced CYP1A1 expression, leading to a chemopreventive effect by inhibiting procarcinogen activation.…”
Section: Discussionmentioning
confidence: 54%